School Management of SD Mutual (Muhammadiyah Satu Alternatif) of Magelang - Suyadi, Suyadi (2011)
This paper has three aims. Firstly, it describes the characteristic of the management of educational personnel at SD Mutual (Muhammadiyah Satu Alternatif) in Magelang. Secondly, it elaborates the characteristic of the management of facilities and infrastructure in SD Mutual (Muhammadiyah Satu Alternatif) of Magelang. And thirdly, this paper intends to the characteristic of learning at SD Mutual (Muhammadiyah Satu Alternatif) of Magelang. It is a qualitative research with ethnography design. The study was limited to the Management of Mutual (Muhammadiyah Satu Alternatif) in Magelang. The main data obtained from informants such as principal, teacher and other support facilities. The method of collecting data by observation, in-depth interview, and documentation methods. Data analysis in this study is an Interactive Model of Analysis. The data validity of this study uses credibility, transferability, dependability, and confirmability test. After analyzing data, the writer gets three findings. The first finding is the characteristics of the management of education personnel at SD Mutual in Magelang has many things that become its characteristic. One of it is the school's effort of improving the quality of SD Mutual Magelang. The effort is an effort to improve the professionalism of education personnel by using training and workshop. The second finding shows the characteristics of the management of facilities and infrastructure have a major impact on improving the quality of education at SD Mutual in Magelang, so that the management of facilities and infrastructure carried out together with all school citizens under the controlling of vice principal of infrastructure and facilities affair and the principal. And the third finding shows that the characteristics of the management of learning is the third factor of improving the quality of learning and education that is done by education personnel of SD Mutual Magelang. It is due to this school applies a PAIKEM GEMBROT method, therefore it can create a qualified learning condition to produce graduates that have a high competence.